Wildlife health management and surveillance in Peru - Elías, Roberto (2020)
Infectious diseases are a serious threat to the conservation of wildlife. In recent years, population growth and environmental changes have significantly increased the frequency of contact of people with wildlife, which together with the change in land use have altered the ecological balance between pathogens and their human hosts. For this reason, the health management and monitoring of wildlife must be implemented in a broader and more comprehensive sense than that currently carried out in our country, which is why there is an urgent need to promote the necessary reforms to reorganize and strengthen of the institution linked to these.